Grooming Teacher Educators And Prospective Teachers In Multicultural Education - Fatma Naqvi, Talmeez (International Journal of Psychosocial Rehabilitation, 2020)
The concept of "learning to live together" lays emphasis on understanding and respect for others, including their belief system, values, and culture. In a diverse nation like India, which celebrates its vibrant mosaic of cultures, it is crucial to provide culturally sensitive education to all students, regardless of their backgrounds. This requires preparing teachers who are attuned to the philosophy of inclusivity and who perceive diversity as an opportunity rather than an obstacle. The present paper aims to explore teacher education programs with a focus on multicultural education and to examine the factors that hinder or promote inclusivity in school-level education. The author reflects on the perceptions of prospective teachers regarding caste-based intelligence differences, highlighting the deep-rooted caste consciousness in Indian society. Though schools are expected to facilitate in the proper growth and development of students, it was found in a number of empirical research and observations that schools often adopt exclusive approaches that perpetuate discrimination. Incidents of discrimination against vulnerable groups have been reported in schools, hindering the democratic ideals that education should uphold. Teachers, as crucial agents in education, can play a transformative role in creating an inclusive and cohesive society. The pedagogical consequences of discriminatory mindsets include low expectations, neglecting students’ needs, and stigmatizing certain students. Multicultural education is essential to address issues of racism, sexism, classism, linguicism, and ableism, religious and racial intolerance. To incorporate multicultural education effectively, teacher education programs should provide cross-cultural experiences and seek to develop teachers as reflective practitioners. Teachers must cultivate cultural competence, understanding the interrelationship between language and culture, and contextual competency. This requires exposure to different cultures, introspection, and an appreciation for cultural diversity. In conclusion, multicultural education should be an integral part of teacher education programs to prepare teachers who can effectively respond to the needs of diverse learners. By embracing multiculturalism, teachers can promote equity, equality, and social justice, contributing to a more inclusive and democratic society.